Dielectric relaxation and freezing effect in Sn₂P₂S₆ - Maior, M.M.; Molnar, Sh.B.; Vrabel, V.T.; Gurzan, M.I.; Motrja, S.F.; Vysochanskii, Yu.M. (Condensed Matter Physics, 2003)
The temperature-frequency studies of dielectric susceptibility in Sn₂P₂S₆,
Sn₂P₂Se₆, (PbySn₁−y)₂P2Se₆ and crystals at low temperatures are reported.
The freezing relaxation dynamics has been observed in a
temperature-frequency dependence of the dielectric properties in the crystals
which are in a polydomain ferroelectric state as well as in the crystals
(PbySn₁−y)₂P₂Se₆ with y > 0.4 which at low temperatures are in the incommensurate
phase. The nature of the effect and its interrelation with
dynamics of ferroelectric domain walls and incommensurate structure is
discussed. В роботі приводяться температурно-частотні дослідження діелектричної проникливості при низьких температурах в кристалах в Sn₂P₂S₆, Sn₂P₂Se₆, (PbySn₁−y)₂P2Se₆. Спостерігалося заморожування релаксаційної динаміки на температурно-частотних залежностях
діелектричних властивостей, як в кристалах які при низьких температурах знаходяться в сегнетоелектричному полідоменному стані,
так і в кристалах (PbySn₁−y)₂P₂Se₆ with y > 0.4, які при низьких температурах знаходяться в неспівмірній фазі. Обговорюється природа
ефекту у взаємозв’язку з сегнетоелектричними доменами і неспівмірною структурою.